Decision Making Analysis Through Profit and Loss Reports (Study of Dewi Bandung Mbawi Bread Factory, Dompu Regency) - Wulandari, Wulandari; Ramadhan, Muh Syahru; Ramadhan, Rizky (Business Management, 2025)
The profit and loss report is one of the financial reports used to assess the financial performance of a company. The information contained in the profit and loss report can be the basis for making business decisions, both for business owners, managers and investors. This research aims to analyze the factors that influence decision making through profit and loss reports at the Dewi Bandung bakery. The approach used in this research is qualitative with a case study method. Data was obtained through in-depth interviews with business owners, financial managers, as well as analysis of financial report documents. The research findings indicate that net profit serves as the primary focus in determining the company’s strategic actions, including investment, expansion, and cost management. In addition, the income statement is also used to assess daily operational efficiency and functions as a monitoring tool for the company's short-term financial condition. Other supporting factors, such as the stability of relationships with customers and the availability of cash flow, also play a role in the decision-making process.